The Rentier Nature of The Iraqi Economy and Its Role In Achieving Economic Development After 2003 - Ibrahim JasimJabbarALyaseri, AqeelAbdulteefAbdulridha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Economic development in developing countries in general and rentier countries, in particular, received significant attention in the 1970s. It played a role in radically changing institutional and social structures and expanding the economicbase. Thus, human well-being has been achieved. The standard of living has improved significantly for society, especially with the oil boom, rising oil prices, and the growing oil rents of crude oil-exporting countries. In Iraq, economic development has relied mainly on oil revenue revenues, indicating the economy's dependence onthe resultingrents. The development plans were prepared during this period under the regime's strategy, political theory, economic philosophy, and programs to achieve economic and social transformations and plan economic growth,which significantly impactedIraq's economic and social conditions. However, after the political change in 2003, successive governments could not achieve economic development commensurate with Iraq's material potential. As a result, what was said to be a slow and faltering development was not achieved in Iraq. Still,Iraq did not experience any structural changes in its economic structures or economic and social institutions, which remain similar to fragile low-income States. Oil revenues did not contribute to the development of the most important productive sectors of the economy but contributed to the underdevelopment of other economic sectors, particularly agriculture and industry. This is due to a series of constraints that have hampered its growth and led to its decline and collapse. There was no clear strategy for economic development in most stages of its development. It negatively affected the Iraqi economy by deteriorating many of its fundamental indicators, makingit vulnerable to fluctuations in the international market due to changes in oil prices. To balance the general budget, reduce reliance on volatile oil revenues, and change public expenditures by changing the budget structure in favor of investment spending. It aimed to expand production capacity and infrastructure, thus employing oil revenues in economic development projects that increase the value of the material asset and generate financial returns.